Validation of the Lupus Nephritis Clinical Indices in Childhood‐Onset Systemic Lupus Erythematosus. Issue 2 (February 2016) - Mina, Rina; Abulaban, Khalid; Klein‐Gitelman, Marisa S.; Eberhard, Barbara A.; Ardoin, Stacy P.; Singer, Nora; Onel, Karen; Tucker, Lori; O'neil, Kathleen; Wright, Tracey; Brooks, Elizabeth; Rouster‐Stevens, Kelly; et al.
Abstract : Objective: To validate clinical indices of lupus nephritis activity and damage when used in children against the criterion standard of kidney biopsy findings. Methods: In 83 children requiring kidney biopsy, the Systemic Lupus Erythematosus Disease Activity Index renal domain (SLEDAI‐R), British Isles Lupus Assessment Group index renal domain (BILAG‐R), Systemic Lupus International Collaborating Clinics (SLICC) renal activity score (SLICC‐RAS), and SLICC Damage Index renal domain (SDI‐R) were measured. Fixed effects and logistic models were calculated to predict International Society of Nephrology/Renal Pathology Society (ISN/RPS) class; low‐to‐moderate versus high lupus nephritis activity (National Institutes of Health [NIH] activity index [AI]) score: ≤10 versus >10; tubulointerstitial activity index (TIAI) score: ≤5 versus >5; or the absence versus presence of lupus nephritis chronicity (NIH chronicity index) score: 0 versus ≥1. Results: There were 10, 50, and 23 patients with ISN/RPS class I/II, III/IV, and V, respectively. Scores of the clinical indices did not differentiate among patients by ISN/RPS class. The SLEDAI‐R and SLICC‐RAS but not the BILAG‐R differed with lupus nephritis activity status defined by NIH‐AI scores, while only the SLEDAI‐R scores differed between lupus nephritis activity status based on TIAI scores. The sensitivity and specificity of the SDI‐R to capture lupus nephritis chronicity was 23.5% and 91.7%, respectively. Despite being designed to measure lupus nephritis activity, SLICC‐RAS and SLEDAI‐R scores significantly differed with lupus nephritis chronicity status. Conclusion: Current clinical indices of lupus nephritis fail to discriminate ISN/RPS class in children. Despite its shortcomings, the SLEDAI‐R appears best for measuring lupus nephritis activity in a clinical setting. The SDI‐R is a poor correlate of lupus nephritis chronicity.